Strategic decision making in business: A systematic review - Jimmi Alexander Farro Acosta,; Luis Miguel Romero Echevarria,; Victor Manuel Figueroa Juarez,; Jose Luis Villegas Chumpitaz,; Carlos Alberto Murillo Salazar, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Strategic decision-making is the systematic process in which organizational leaders evaluate and select options that determine the organization's long-term direction. The study was based on basic research, a qualitative approach, a systematic review, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The inquiry evidenced those strategic decisions, supported by data analysis and adaptive management, improve companies' competitiveness and long-term sustainability, ensuring their resilience and success in the face of future challenges. Thus, it was concluded that strategic decision-making should be approached as a fundamental process that involves selecting an option among various alternatives to achieve specific goals; however, its implementation requires effective information management and continuous strategic evaluation, with companies needing to adjust their strategies to ensure long-term sustainability and competitiveness.